2020
DOI: 10.1186/s12939-020-01220-5
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for small area prevalence estimation based on survey data

Abstract: Background: Brazil conducts many health surveys to provide estimates by national level, macro-regions, states, metropolitan regions and capitals. However, estimates for smaller areas are lacking due to their high cost. The Health Vulnerability Index (in Portuguese, Índice de Vulnerabilidade em Saúde, IVS) is a measure that combines socioeconomic and environmental variables in the same indicator and allows for the analysis of the characteristics of population groups residing in census tracts, grouping them into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…. More detailed information on the direct method of estimation for small areas employed can be obtained in another publication 10 . The difference in the prevalence of regular FV consumption, LTPA practice, and binge drinking between the IVS groups was statistically verified by the Student's t-test, with a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. More detailed information on the direct method of estimation for small areas employed can be obtained in another publication 10 . The difference in the prevalence of regular FV consumption, LTPA practice, and binge drinking between the IVS groups was statistically verified by the Student's t-test, with a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Brazil has national surveys that make it possible to measure numerous health events. However, due to costs, the sampling used generally estimates large areas, such as the Federated Units, reaching up to the capitals at most, failing to estimate small areas, nor identifying intra-urban inequalities 10 . Thus, it is necessary to advance the knowledge of the differences in the distribution of health events in different population groups, aiming to support policies to reduce inequalities in health 11 .…”
Section: Introductionmentioning
confidence: 99%
“…NCD and their risk factors have been monitored in the country by large national surveys, which are essential to aggregate evidence on individual and collective health 6,7 ; however, national surveys do not allow estimates by municipalities or for smaller areas within the sampled cities. Thus, it is necessary to advance the monitoring of these diseases in small geographic areas, in order to identify the existing inequalities, which are often masked by national or state average statistics 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Estimates for small areas can help managers in public health in planning, defining intervention priorities and allocating resources, in addition to identifying possible decentralized solutions to the diagnosed problems, which may include social, cultural, legal, political or health-related approaches in small areas 8,9 . The use of composite indicators in the health RESUMO: Objetivo: Estimar as prevalências de hipertensão e diabetes para pequenas áreas em Belo Horizonte, MG, segundo o índice de vulnerabilidade da saúde (IVS).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-quality methodologies can help assess the impact of health policies with greater precision. The paper by Tomie Ivata Bernal et al [ 16 ] illustrates how the use of a small-area prevalence estimation identified that the reduction in tobacco prevalence in Brazil was more common in high-income areas than it was in the lower-income areas. The ability to replicate these approaches to use more granular information may foster better local policies.…”
mentioning
confidence: 99%